On the Link Between Global Volcanic Activity and Global Mean Sea Level - Dumont, Stéphanie; Petrosino, Simona; Neves, Maria C. (Frontiers in Earth Science, 2022)
Studying a large number of volcanic eruptions is a way to decipher general characteristics related to volcano dynamics but also on external forcing influencing it, such as solid Earth and ocean tides. Many studies have tackled this tidal influence on the onset of volcanic eruptions and more generally, on volcanic activity. However, the interplay between this quasi-permanent forcing and volcanic systems is still poorly understood. With the present study, we propose to consider a global viewpoint to address this interaction. We analyzed the number of monthly volcanic eruptions and the global mean sea level between 1880 and 2009 using the Singular Spectrum Analysis time-series analysis technique to evaluate the existence of common periodicities. We found multi-decadal components of similar periodicities present in both time-series which we link to those already recognized in the polar motion. Its multi-decadal variations result in a mass reorganization in the oceans whose associated stress changes may impact processes generating volcanic eruptions worldwide. Our results show the influence of global processes on volcanic activity and open many questions to further investigate these multi-scale interactions.